IMPACTS OF CYPERMETHRIN ON HISTOPATHOLOGY OF LIVER AND GILLS OF FRESH WATER FISH Anabas testudineus - JHA, AMIT KUMAR; ., ANUPAMA; MISHRA, KALI CHARAN (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
Synthetic pyrethroids are very potent insecticides that have gained strong market share during recent years. Pyrethroids are known for its low mammalian toxicity and short environmental persistence due to their rapid decomposition on exposure to the metabolizing systems. The present study was carried out to investigate the histopathological changes in liver and gills of a fresh water fish Anabas testudineus under exposure of a pyrethroid insecticide cypermethrin. Acute toxicity of cypermethrin to the fish was determined for 24, 48, 72 and 96 hours by regression equation. The LC50 value were calculated 0.15 ppm, 0.20 ppm, 0.25 ppm and 0.30 ppm respectively. The sublethal concentration was 0.106 ppm during present work. After exposure period of 30 days significant changes were reported in liver and gills of cypermethrin exposed fishes. Hyperamia, liquefactive necrosis, dilation of sinusoidal spaces and splitting of hepatocytes were reported in liver. Liquefaction, breakage of gill lamella and hypertrophy of mucous cells were observed in the gills. In the present investigation it was reported that the cypermethrin badly affects the liver and gills of fish even in low dose.